Government Spending Multipliers in Developing Countries : Evidence from Lending by Official Creditors - Kraay, Aart (American Economic Association, 2015)
The author uses a novel loan-level dataset covering lending by official creditors to developing country governments to construct an instrument for government spending. Loans from official creditors typically finance multiyear public spending projects, with disbursements linked to the stages of project implementation. The identification strategy exploits the long lags between approval and eventual disbursement of these loans to isolate a predetermined component of public spending associated with past loan approval decisions taken before the realization of contemporaneous shocks. In a large sample of 102 developing countries over the period 1970-2010, the one-year spending multiplier is reasonably-precisely estimated to be around 0.4.